2015
DOI: 10.1142/s021881041572020x
|View full text |Cite
|
Sign up to set email alerts
|

Thumb Carpometacarpal Joint Stabilization in Ehlers-Danlos Syndrome - Case Report

Abstract: We report the case of an 18-years-old patient with thumb carpometacarpal ligament laxity due to Ehlers-Danlos syndrome who was treated with trapezial opening wedge osteotomy combined with volar ligaments reconstruction. Two years postoperatively she is pain free and the thumb carpometacarpal joint is stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Similarly, two other case studies of children with hEDS also indicated pain in the fingers, specifically due to painful subluxation of the carpometacarpal joint of the thumb [40]. Such pain in smaller joints has also been reported among older adolescents with EDS, wherein a case study of an 18-year-old woman with hEDS indicated substantial finger pain, specifically of the thumb due to frequent dislocations [41]. Pain in smaller joints is also reported in children with JHS, with 32% indicating wrist pain [37].…”
Section: Sites Of Pain: Musculoskeletalmentioning
confidence: 74%
“…Similarly, two other case studies of children with hEDS also indicated pain in the fingers, specifically due to painful subluxation of the carpometacarpal joint of the thumb [40]. Such pain in smaller joints has also been reported among older adolescents with EDS, wherein a case study of an 18-year-old woman with hEDS indicated substantial finger pain, specifically of the thumb due to frequent dislocations [41]. Pain in smaller joints is also reported in children with JHS, with 32% indicating wrist pain [37].…”
Section: Sites Of Pain: Musculoskeletalmentioning
confidence: 74%
“…Increases in grip and pinch strength status post bilateral tendon interpositional thumb arthroplasty has been previously noted in a case study in the setting of EDS (Badia et al., 2005). Similarly, a case study describing trapezial opening wedge osteotomy and volar ligament reconstruction in the setting of painful CMC subluxation and crepitus demonstrated a grip strength improvement of 18 kg at 2 years postoperatively in the patient (Breahna and Meads, 2015). These studies, in addition to our findings, suggest a trend towards increased thumb strength following reconstructive surgeries for CMC arthritis in the setting of EDS.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, there is little known of the natural history of CMC arthritis in the setting of EDS. A literature review yielded two case reports with follow-up beyond 1 year; an 18 year old managed with trapezial opening wedge osteotomy and volar ligament reconstruction, and a middle-aged patient with bilateral tendon interposition arthroplasty (Badia et al., 2005; Breahna and Meads, 2015). As such, there remains little evidence-based guidance when deciding on treatment route and discussing the prognosis of EDS-related CMC arthritis.…”
Section: Introductionmentioning
confidence: 99%